1996
DOI: 10.1121/1.415428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of static pressure on acoustic transmittance of Albunex(R) microbubble suspensions

Abstract: Albunex (ALX), an albumin-stabilized microbubble echo contrast agent, is sensitive to pressures similar to those produced by the heart. The tested hypothesis was that the acoustic transmittance of ALX suspensions will increase with increasing hydrostatic pressure (Ps). The test involved an acoustic setup analogous to a spectrophotometer. The acoustic transmittance of microbubble suspensions was strongly Ps dependent. Transmittance at 1 MHz was essentially zero at ambient pressure, increasing to approximately 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…Further, it was seen that the contrast reduction was an irreversible process. Gottlieb et al [52] and Brayman et al [53] reported similar observations.…”
Section: Blood Pressurementioning
confidence: 65%
“…Further, it was seen that the contrast reduction was an irreversible process. Gottlieb et al [52] and Brayman et al [53] reported similar observations.…”
Section: Blood Pressurementioning
confidence: 65%
“…This allowed better imaging of the various organs, but also opened up other objectives (e.g., the measurement of pressure). The use of UCAs for noninvasively measuring blood pressure in specified locations within the cardiovascular system is a promising clinical application (Shapiro et al 1990;Brayman et al 1996;Bouakaz et al, 1999). The first attempts to use US and air bubbles to measure blood pressure (Fairbank and Scully 1977;Hok 1981;Shankar et al 1986) proved the concept, but it could not be implemented because the bubbles dissolved very fast.…”
Section: Introductionmentioning
confidence: 99%
“…Then, they investigated ambient pressure dependent dissolution time of these free bubbles for local blood pressure estimation and reported a sensitivity of 50 mm Hg. Brayman et al 33 found that transmission through air based contrast agent Albunex drastically reduced with ambient pressure increase due to the bubble destruction. Intrinsic limitations in sensitivity of these techniques prevented their clinical implementation.…”
Section: Introductionmentioning
confidence: 99%